2015
DOI: 10.1037/a0035181
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing simulated from genuine dissociative identity disorder on the MMPI-2.

Abstract: Due to high elevations on validity and clinical scales on personality and forensic measures, it is challenging to determine if individuals presenting with symptoms of dissociative identity disorder (DID) are genuine or not. Little research has focused on malingering DID, or on the broader issue of the profiles these patients obtain on the Minnesota Multiphasic Personality Inventory (MMPI-2), despite increasing awareness of dissociation. This study sought to characterize the MMPI-2 profiles of DID patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 37 publications
(70 reference statements)
4
57
0
3
Order By: Relevance
“…The SIMS includes subscales assessing amnesia as well as affective, psychotic, and neurological symptoms. Although affective, psychotic and neurological symptoms may be rare in some patient groups, they are well documented as common symptoms among individuals with DID . For example, individuals with DID have many intrusion symptoms that Schneider would have described as classic symptoms of schizophrenia and several studies have documented that the first‐rank symptoms for schizophrenia are as common in DID .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The SIMS includes subscales assessing amnesia as well as affective, psychotic, and neurological symptoms. Although affective, psychotic and neurological symptoms may be rare in some patient groups, they are well documented as common symptoms among individuals with DID . For example, individuals with DID have many intrusion symptoms that Schneider would have described as classic symptoms of schizophrenia and several studies have documented that the first‐rank symptoms for schizophrenia are as common in DID .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the Fantasy Model , also referred to as the sociocognitive or non‐trauma‐related model , posits that dissociation and DID are related to enactment, sleep disturbances, suggestive psychotherapy, and/or sociocultural influences and are mediated by high suggestibility and fantasy proneness. The Fantasy Model states that DID can easily be simulated, but several studies comparing DID simulators to individuals with genuine DID have found that groups can be distinguished, contradicting the Fantasy Model . On the other hand, some studies examining differences on psychological measures found that DID‐simulating healthy controls can imitate some of the most obvious and well‐known symptoms associated with DID such as psychoform dissociation, including phenomena such as amnesia, loss of control, and identity confusion, yet simulators fail to adequately present the subtle and less well‐known symptoms and associated features of DID .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 53 DID patients’ MMPI-2 [ 119 ] profiles, the highest elevation occurred on scale Schizophrenia (8) with additional marked elevations (>70 T) on scales Depression (2), Paranoia (4), Psychopathic Deviate (6), and Psychasthenia (7) which measures anxiety [ 120 ]. The DID Schizophrenia-Depression- code type has been found in previous DID samples [ 121 ], although Schizophrenia combined with Paranoia or Psychopathic Deviate (due to family discord and self-alienation, rather than problems with authority) are also common [ 122 125 ].…”
Section: Reviewmentioning
confidence: 99%